2020
DOI: 10.1111/jcms.12980
|View full text |Cite
|
Sign up to set email alerts
|

Juncker's Curse? Identity, Interest, and Public Support for the Integration of Core State Powers

Abstract: In this study we analysed the patterns and covariates of public support for the European integration of core state powers based on an original new survey. We found considerable variation across integration instruments, member states and policy issues. Horizontal transfers are supported more than vertical capacity building; member states from the EU's South‐East are more supportive than states from the North‐West; and support increases from debt relief to unemployment assistance, sharing the burdens of refugees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
(50 reference statements)
0
24
0
Order By: Relevance
“…In doing so, the authors use an original dataset on public preferences for integration of core state powers collected in spring, 2018 in a selection of European countries. While the survey lacks a specific measurement of the collective identification of the respondents, Bremer et al (2020) proxy it by looking, in particular, at the preferences of voters of populist radical right parties, which typically correlate with self-reported exclusive nationalism (although they cannot be considered completely equivalent, as exclusive nationalists are also found among the electorates of other parties). While they do not find generalized opposition to the integration of core state powers, they do find specific opposition in certain countries and among certain voters.…”
Section: The Structure Of This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…In doing so, the authors use an original dataset on public preferences for integration of core state powers collected in spring, 2018 in a selection of European countries. While the survey lacks a specific measurement of the collective identification of the respondents, Bremer et al (2020) proxy it by looking, in particular, at the preferences of voters of populist radical right parties, which typically correlate with self-reported exclusive nationalism (although they cannot be considered completely equivalent, as exclusive nationalists are also found among the electorates of other parties). While they do not find generalized opposition to the integration of core state powers, they do find specific opposition in certain countries and among certain voters.…”
Section: The Structure Of This Special Issuementioning
confidence: 99%
“…The open question is, therefore, whether there is a sufficient identity reservoir for the European exertion of core state powers, and how these relate to specific policy fields. Before moving towards a sector specific analysis, the third article – co‐authored by Björn Bremer, Philipp Genschel, and Markus Jachtenfuchs () – provides a horizontal exploration of the relationship between public preferences for integration in several fields of core state competence and exclusive nationalism. In doing so, the authors use an original dataset on public preferences for integration of core state powers collected in spring, 2018 in a selection of European countries.…”
Section: The Structure Of This Special Issuementioning
confidence: 99%
“…While usually these works focus on fiscal or transnational solidarity, the conceptualization and measurement of solidarity differ highly, and we find varying results regarding the level of public support for solidarity actions. While Lahusen and Grasso ( 2018 ) find limited public support for EU-wide solidarity actions, other authors argue that more solidarity is found in the EU than perhaps first expected (Bremer et al 2020 ; Ferrera and Burelli, 2019 ; Genschel and Hemerijck 2018 ; Gerhards et al 2019 ). These analyses, while using different operationalizations, find substantial deviation across Member States, their policy issues, and instruments.…”
Section: Research On Solidarity In the European Unionmentioning
confidence: 99%
“…These analyses, while using different operationalizations, find substantial deviation across Member States, their policy issues, and instruments. The results are often contradictory (Bremer et al 2020 ; Ferrera and Burelli 2019 ; Genschel and Hemerijck 2018 ; Lahusen and Grasso 2018 ). 4 Specifically focusing on public opinion in the EU, the work of Genschel and Hemerijck ( 2018 , p. 4) found that many survey participants when questioned on support for an over-indebted Member State expressed confusion and ambiguity.…”
Section: Research On Solidarity In the European Unionmentioning
confidence: 99%
“…Bremer et al . () describe two approaches: one based on policy area and another based on power resources. In the policy‐based approach, policy areas are perceived to differ on the basis of how important they are for defining a state as a sovereign entity.…”
Section: Historical Benchmarks and Support For European Cooperationmentioning
confidence: 99%